FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN - Liliana C.D.T. Duarte, 12.05.52.0216; Puspitasari, Elen (Students' Journal of Accounting and Banking, 2018)
This study was conducted with the aim to analyze the influence of factors that affect the profitability. Independent variables used in this research are capital adequacy ratio, loan to deposit ratio, operational cost and operating income, non performing loan, net interest margin and third party fund, while the dependent variable used is profitability.The data used in this study is the data of Indonesian Banking Companies listed on the Indonesia StockExchange during the year 2013-2016. Methods in the selection of samples in this study using purposive sampling method with the aim to obtain a sample in accordance with research objectives. The sample of this research is 142 Observations on Indonesian Banking Companies in Indonesia Stock Exchange. The hypothesis in this study was tested by using multiple linear regression analysis tools with confidence level of 95%.The result of theresearch shows that: Capital Adequacy Ratio has a significant negative effect to profitability, Loan To Deposit Ratio have significant positive effect to profitability, Operational Cost and Determination of Operation have negative significant effect to profitability, Non Performing Loan has positive significant effect on Net Interest Margin profitability positive significant to profitability and Third Party Fund have positive significant to profitabilityKeywords: capital adequacy ratio, loan to deposit ratio, operational cost and operating income, non performing loan, net interest margin and third party fund